Lifecycle Ecology of Deep-Sea Chemosymbiotic Mussels: A Review - Laming, Sven R.; Gaudron, Sylvie M.; Duperron, Sébastien (Frontiers in Marine Science, 2018)
Mussels within the subfamily Bathymodiolinae, in particular the larger Bathymodiolus species (sensu lato) thriving at cold seeps and hydrothermal vents, are among the most iconic fauna to colonise deep-sea reducing habitats globally. Fuelled by energy derived from chemosynthetic symbioses, their contribution to ecosystem productivity is conspicuous, with many bathymodioline species forming dense, extensive aggregates. Chemosymbiotic mussels play crucial roles as ecosystem engineers, both through the formation of spatially heterogeneous biogenic reefs and in redistributing reduced-fluid emissions. The notable absence of Bathymodiolinae outside of reducing ecosystems affirms their dependency on these ephemeral habitats, placing spatiotemporal constraints on dispersal to, and colonisation of nascent, chemosynthetically active substrata. Thus, although symbioses may explain why these mussels are so productive in deep-sea reducing habitats, species’ survival over successive generations depends largely upon the adaptive characteristics of their lifecycle as a whole. Despite accumulating data on the biology and ecology of adults however, details remain fragmented regarding earlier developmental junctures during their complex lifecycles. This paper therefore brings together results from research undertaken over recent years on this topic, providing a synthesis of various lifecycle aspects of bathymodiolins from the earliest stages of development, gametogenesis, through to sexual maturity, including the intrinsic, emerging role of symbionts. The review provides a comprehensive overview of our current understanding and identifies areas where further study into these keystone organisms is warranted. The benefits of applying a lifecycle-integrated approach when evaluating the potential impacts of global change and the various activities that ultimately threaten habitats on deep-sea fauna are then discussed.